Ly6G+ neutrophil-derived miR-223 inhibits the NLRP3 inflammasome in mitochondrial DAMP-induced acute lung injury - Feng, Zunyong; Qi, Shimei; Zhang, Yue; Qi, Zhilin; Yan, Liang; Zhou, Jing; He, Fang; Li, Qianqian; Yang, Yanyan; Chen, Qun; Xiao, Shi; Li, Qiang; et al. (Cell death & disease, 2017)
MicroRNA (miRNA) mediates RNA interference to regulate a variety of innate immune processes, but how miRNAs coordinate the mechanisms underlying acute lung injury/acute respiratory distress syndrome (ALI/ARDS) in patients with pulmonary inflammatory injury is still unknown. In this study, we demonstrated that miR-223 limits the number of Ly6G+ neutrophils and inhibits the activity of the NLRP3 inflammasome to alleviate ALI induced by mitochondrial damage-associated molecular patterns (DAMPs) (MTDs). miR-223 expression is increased in the lungs of MTD-induced mice or ARDS patients following trauma/transfusion or following the physiological remission of ALI/ARDS. miR-223−/+ mice exhibited more severe ALI and cytokine dysregulation. Other studies have shown that MTD-induced increases in miR-223 expression are mainly contributed by Ly6G+ neutrophils from the haematopoietic system. miR-223 blocks bone marrow-derived Ly6G+ neutrophil differentiation and inhibits peripheral cytokine release. In addition, MTD-induced miR-223 expression activates a negative feedback pathway that targets the inhibition of NLRP3 expression and IL-1 β release; therefore, miR-223 deficiency can lead to the sustained activation of NLRP3-IL-1 β . Finally, elimination of peripheral Ly6G+ neutrophils and pharmacological blockade of the miR-223–NLRP3–IL-1 β signalling axis could alleviate MTD-induced ALI. In summary, miR-223 is essential for regulating the pathogenesis of DAMP-induced ALI.